Rancang Bangun Cooler Box Termoelektrik dengan Air Sterilizer sebagai Tempat Pengiriman Air Susu Ibu (ASI) - Gostsa Khusnun Naufal (Jurnal Engine: Energi, Manufaktur, dan Material, 2019)
The growing trend today is the exclusive breast milk given to the baby until the baby has a sufficient age. This is certainly not too problematic for housewives who most of the time are at home, so it can menyusi baby without interference. But this is different from career women who have babies and want to provide exclusive breast milk, a great distance between home and workplace and time constraints become a barrier factor that makes exclusive breast milk becomes very difficult given career woman to her child. Cooler box can keep asi temperature remain in cold condition prevent damage of breast milk content. Inside the cooler box put ice gel to keep the temperature cool. The ice gel can keep the temperature cool for 3-4 hours. Another problem is the hygiene of the cooler box and storage container from the breast milk. Not infrequently the cooler box into a source of bacteria that can spread to the breast milk contained in the cooler box, this can be caused moisture or from the hands that are not sterile. This is because in the process of pumping and transfer into the cooler box is still using the manual by hand. The researcher will design a cooler box build by using thermoelectric as cooling from cooler box and have water sterilizer, which is useful to decrease the amount of bacteria by using uv light. Low levels of bacteria will make the cooler box becomes more hygienic as a storage area when it will be shipped.